Host cellular factors involved in pseudorabies virus attachment and entry: a mini review - Tan, Lei; Wang, Kaixin; Bai, Ping; Zhang, Shuo; Zuo, Mengting; Shu, Xianghua; Wang, Aibing; Yao, Jun (Frontiers in Veterinary Science, 2023)
Pseudorabies virus (PRV) belongs to the Alphaherpesvirinae subfamily and serves as an exceptional animal model for investigating the infection mechanism of Herpes simplex virus type 1. Notably, PRV has the capability to infect a wide range of mammals, including humans, highlighting its potential as an overlooked zoonotic pathogen. The attachment and entry steps of PRV into host cells are crucial to accomplish its life cycle, which involve numerous cellular factors. In this mini review, we offer a comprehensive summary of current researches pertaining to the role of cellular factors in PRV attachment and entry stages, with the overarching goal of advancing the development of novel antiviral agents against this pathogen.